UNSUR INTRINSIK DAN NILAI PENDIDIKAN KARAKTER DALAM SERAT WULANGREH PUPUH SINOM SERTA RELEVANSINYA SEBAGAI MATERI AJAR BAHASA JAWA DI SEKOLAH MENENGAH PERTAMA - Wulandari, Novita Ayu; Sumarwati, Sumarwati; Rakhmawati, Ani (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
This research were aims to describe the physical element, describe the inner element, describe the value of character education, and describe the relevance of the intrinsic elements of the analysis and the value of character education in Serat  Wulangreh pupuh Sinom and its relevance as a matter of learning the Javanesse language in junior high school. This study is a qualitative research approach with analysis contents. From the results of the analysis of the data obtained a summary of that element of intrinsic Serat Wulangreh pupuh Sinom consists of inner and physical structure. Physical structure is diction of vocabulary, use of the kawi language form of words are tembung garba, tembung plutan and wancahan, the use of passive form (den, infix-in-), use of suffixes – ipun,-ira, and –neki, then use of prefixes nasal and tembung baliswara. The imaginary include visual, auditory, and kinesthetic. Concrete words that indicate the actual meaning of the word, figurative language include hiperbola and the symbolism of objects. Rima include purwakanthi swara, purwakanthi sastra, and purwakanthi basa. Metrum includes paugeran guru wilangan, guru gatra and guru lagu. Typography using conventional typography. Inner structure is themes and a message. The theme of Serat Wulangreh pupuh Sinom is the grammar rules of behavior and a message contain message author about how it should behave towards yourself, other people and toward God. The value of character education includes values of honesty, hard work, religious values, the values of peace, the values of responsibility, the spirit of nationality and love for the motherland. Analysis of the intrinsic element and the value of character education in Serat Wulangreh pupuh Sinom worthy and relevant material to serve as learning the Javanesse language in junior high school in class VII semester II at KD 3.2 and KD 4.2.